PERAN FASILITAS OLAHRAGA SEKOLAH DALAM PARTISIPASI DAN MINAT BEROLAHRAGA - Ahmad Wildan; Ikhsan Maulana Putra; Raja Bani Pilitan; Desi Tri Susanti; Jhony Hendra (ADIBA : JOURNAL OF EDUCATION, 2025)
The availability of sports facilities at schools plays a crucial role in encouraging student participation and interest in sports. However, in reality, some schools still have limited facilities, resulting in low student engagement in physical activities. Based on this situation, This study seeks to ascertain how sports facilities affect the participation and interest in sports among vocational high school students in Merangin Regency. This study combined a survey method with a quantitative approach. Purposive sampling was used to pick 81 students for the sample size. A questionnaire was used as the study tool to gauge amenities, participation, and interest in sports. Data analysis was performed using tests with a significance threshold of 0.05 using SPSS. The results showed that sports facilities significantly influenced student participation with a regression coefficient of 0.097 and a significance value of 0.000. Furthermore, facilities also significantly influenced student interest in sports, with a significance value of 0.004 and a regression coefficient of 1.286. Therefore, the better the facilities available, the higher the student participation and interest in participating in sports activities at school.